Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure! Let's find the missing entries in the given table for the equation \(9x - 6y = 18\). We will determine the \(y\) values corresponding to the given \(x\) values and the \(x\) value corresponding to the given \(y\) value.
### Step 1: Solve for \(y\) when \(x = 1\)
Substitute \(x = 1\) into the equation \(9x - 6y = 18\):
[tex]\[ 9(1) - 6y = 18 \implies 9 - 6y = 18 \][/tex]
[tex]\[ -6y = 18 - 9 \implies -6y = 9 \][/tex]
[tex]\[ y = \frac{9}{-6} \implies y = -\frac{3}{2} \implies y = -1.5 \][/tex]
So, when \(x = 1\), \(y = -1.5\).
### Step 2: Solve for \(y\) when \(x = 0\)
Substitute \(x = 0\) into the equation \(9x - 6y = 18\):
[tex]\[ 9(0) - 6y = 18 \implies 0 - 6y = 18 \][/tex]
[tex]\[ -6y = 18 \][/tex]
[tex]\[ y = \frac{18}{-6} \implies y = -3 \][/tex]
So, when \(x = 0\), \(y = -3\).
### Step 3: Solve for \(y\) when \(x = 3\)
Substitute \(x = 3\) into the equation \(9x - 6y = 18\):
[tex]\[ 9(3) - 6y = 18 \implies 27 - 6y = 18 \][/tex]
[tex]\[ -6y = 18 - 27 \implies -6y = -9 \][/tex]
[tex]\[ y = \frac{-9}{-6} \implies y = \frac{3}{2} \implies y = 1.5 \][/tex]
So, when \(x = 3\), \(y = 1.5\).
### Step 4: Solve for \(x\) when \(y = 0\)
Substitute \(y = 0\) into the equation \(9x - 6y = 18\):
[tex]\[ 9x - 6(0) = 18 \implies 9x - 0 = 18 \][/tex]
[tex]\[ 9x = 18 \][/tex]
[tex]\[ x = \frac{18}{9} \implies x = 2 \][/tex]
So, when \(y = 0\), \(x = 2\).
### Summary
The completed table with the missing entries is:
[tex]\[ \begin{tabular}{|l|l|l|l|l|} \hline [tex]$x$[/tex] & 1 & 0 & 3 & 2 \\
\hline [tex]$y$[/tex] & -1.5 & -3 & 1.5 & 0 \\
\hline
\end{tabular}
\][/tex]
Thus, the values of the missing entries satisfy the given equation.
### Step 1: Solve for \(y\) when \(x = 1\)
Substitute \(x = 1\) into the equation \(9x - 6y = 18\):
[tex]\[ 9(1) - 6y = 18 \implies 9 - 6y = 18 \][/tex]
[tex]\[ -6y = 18 - 9 \implies -6y = 9 \][/tex]
[tex]\[ y = \frac{9}{-6} \implies y = -\frac{3}{2} \implies y = -1.5 \][/tex]
So, when \(x = 1\), \(y = -1.5\).
### Step 2: Solve for \(y\) when \(x = 0\)
Substitute \(x = 0\) into the equation \(9x - 6y = 18\):
[tex]\[ 9(0) - 6y = 18 \implies 0 - 6y = 18 \][/tex]
[tex]\[ -6y = 18 \][/tex]
[tex]\[ y = \frac{18}{-6} \implies y = -3 \][/tex]
So, when \(x = 0\), \(y = -3\).
### Step 3: Solve for \(y\) when \(x = 3\)
Substitute \(x = 3\) into the equation \(9x - 6y = 18\):
[tex]\[ 9(3) - 6y = 18 \implies 27 - 6y = 18 \][/tex]
[tex]\[ -6y = 18 - 27 \implies -6y = -9 \][/tex]
[tex]\[ y = \frac{-9}{-6} \implies y = \frac{3}{2} \implies y = 1.5 \][/tex]
So, when \(x = 3\), \(y = 1.5\).
### Step 4: Solve for \(x\) when \(y = 0\)
Substitute \(y = 0\) into the equation \(9x - 6y = 18\):
[tex]\[ 9x - 6(0) = 18 \implies 9x - 0 = 18 \][/tex]
[tex]\[ 9x = 18 \][/tex]
[tex]\[ x = \frac{18}{9} \implies x = 2 \][/tex]
So, when \(y = 0\), \(x = 2\).
### Summary
The completed table with the missing entries is:
[tex]\[ \begin{tabular}{|l|l|l|l|l|} \hline [tex]$x$[/tex] & 1 & 0 & 3 & 2 \\
\hline [tex]$y$[/tex] & -1.5 & -3 & 1.5 & 0 \\
\hline
\end{tabular}
\][/tex]
Thus, the values of the missing entries satisfy the given equation.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.